The Anatomy of a Witch: Lessons in English Language, Literature and Improvisation - Željka (Nemet); Jelena Kovačević (CLELEjournal, 2015)
The paper provides a brief outline of the historical development, principles and implementation of improvisational theatre in both the theatrical and non-theatrical context in order to present the art of improvisation as a strategy in foreign and second language acquisition. Research shows that because of the adaptability of the improvisational game structure which allows for the applicability of improvisational techniques in different contexts and with subjects of various backgrounds, improvisational theatre can be incorporated in teaching an array of subjects and topics, including English as a foreign and second language. In order to demonstrate the possible application of the improvisational strategy in English language teaching, there is a detailed description of an interdisciplinary workshop The English Anatomy of a Witch, focusing on the oral tradition of storytelling and the fairy tale as the direct product of both storytelling and improvisational practices, which contains different aspects of improvisational techniques in the classroom setting. By discussing the figure of the witch, which is anthropologically and historically present in British and American culture, the workshop aims to achieve a number of goals and objectives pertaining to both foreign and second language acquisition, the re-evaluation of the literary tradition, as well as pedagogies that foster critical and divergent thinking.